LEVEL OF BEHAVIORAL DEVIATIONS AMONG THE TALENTED STUDENTS IN THE ADOLESCENCE STAGE AND THEIR RELATIONSHIP WITH SOME PERSONAL VARIABLES IN THE KINGDOM OF SAUDI ARABIA (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
The present study aims to identify the nature of the relationship between patterns of family upbringing and the deviant behavior among the talented students in the city of Jeddah in Saudi Arabia. The study has been applied to the talented students in the age (13-15) years and to their parents. A scale of family upbringing patters and a scale of behavioral deviations have been developed in order to achieve the study objectives. The study has reached into the conclusion that the relationship between patterns of family upbringing and deviant behavior interpret as a ratio of (27.0 %) of the deviant behavior in all patterns of upbringing.